Redessine-moi… l'Afrique - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Demain l'Afrique : le cauchemar ou l'espoir? Éditions Complexe, Bruxelles (1998) 234 pages Prix : 139 FF / E21, 55